Program kredit ultra mikro dan kemiskinan di Jawa Tengah pada masa pandemi - Karnoto, Suparjito Bin (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2021)
This study focuses on the role of financing the ultra microprogram (UMi) to support government programs in poverty alleviation. There are two analyzes used: first descriptive analysis, which compares the number of micro-enterprises with the number of poor people in Central Java. Second, statistical analysis of Pearson correlation measures the correlation between the number of micro-entrepreneurs, the amount of ultra-micro credit financing disbursement, the number of poor people, and indicators related to poverty. The results of the descriptive analysis show that before the covid-19 pandemic, the average percentage of micro-enterprises and the number of poor people was 4.09 percent. In comparison, during the covid-19 pandemic, the average was 5.40 percent. Pearson correlation statistical analysis shows that the number of customers and the distribution of ultra-micro credit strongly correlate with the number of poor people. The number of poor people has a strong correlation with life expectancy and an average length of schooling. It has a reasonably strong correlation with other indicators related to poverty both before the 2019 COVID-19 pandemic and during the 2020 COVID-19 pandemic.